Coupling and Dearomatization of Pyridines at a Transient η2‐Cyclopropene/Bicyclobutane Zirconocene Complex. Issue 62 (16th October 2017) - Romero, Nuria; Dufrois, Quentin; Vendier, Laure; Dinoi, Chiara; Etienne, Michel
Abstract: This paper reports on stereospecific coupling reactions between an η 2 ‐cyclopropene ligand and pyridine derivatives, which are preferred to alternative C−H bond activation reactions. The dicyclopropylzirconocene complex [Cp2 Zr( c ‐C3 H5 )2 ] (1 ) eliminates cyclopropane to generate the η 2 ‐cyclopropene/bicyclobutane intermediate [Cp2 Zr(η 2 ‐ c ‐C3 H4 )] (A ).A does not activate any pyridine C−H bonds, but rather pyridine inserts into a Zr−C bond ofA, yielding an azazirconacycle with a dearomatized pyridyl group [Cp2 Zr{κ 2 ‐N, C 8 ‐(2‐ c ‐C3 H4 )‐C5 H5 N}] (2 ). Kinetic data, isotopelabelling experiments, and DFT calculations indicate that the rate‐determining step of this stereospecific reaction is cyclopropane elimination, and that the stability of the intermediate [Cp2 Zr(η 2 ‐ c ‐C3 H4 )(NC5 H5 )] (A‐py ) governs the selectivity of the reaction. Complex 2 tautomerizes to [Cp2 Zr{κ 2 ‐N, C 8 ‐(2‐C3 H5 )‐C5 H4 N}] (6 ) through a base‐catalyzed proton migration accompanied by cyclopropyl opening and restoration of conjugation within the zirconacycle. Abstract : The Odd Couple : Diastereospecific coupling of pyridine with a transient η 2 ‐cyclopropene zirconocene complex takes precedence over C−H bond activation, an alternative pathway observed for other heteroaromatics